KONTRIBUSI PENDAPATAN USAHATANI KELOR ANGGOTA KELOMPOK TANI MAJU BERSAMA TERHADAP PENDAPATAN USAHATANI DI DESA NOELBAKI KECAMATAN KUPANG TENGA KABU PATEN KUPANG - Lay, Cindy Loranza; Suek, Johanna; Nampa, I Wayan (Undana Press, 2024)
Moringa farming has great potential in Kupang Regency, but economically its role in overall farming income is not yet known. A study on the contribution of moringa farming income of members of farmer groups to the overall income of the farm was carried out to determine the role of moringa farming. On the income of moringa farmers. The research was conducted in Noelbaki Village, Kupang Regency with 20 farming households. The research results show that the role of moringa farming in the household economy is 44.45% lower than non-moringa farming income of 55.65%. This role is smaller than the role of farming other than moringa on farmers' household income. Even though it has a relatively low contribution, moringa farming has sufficient development potential.